2012
DOI: 10.1681/asn.2011050493
|View full text |Cite
|
Sign up to set email alerts
|

Genetic or Pharmacologic Blockade of EGFR Inhibits Renal Fibrosis

Abstract: Although enhanced activation of the EGF receptor (EGFR) associates with the development and progression of renal fibrosis, the mechanisms linking these observations are not completely understood. Here, after unilateral ureteral obstruction (UUO), wild-type mice exhibited sustained EGFR phosphorylation in the kidney and developed renal fibrosis that was more severe than the renal fibrosis observed in waved-2 mice, which have reduced EGFR tyrosine kinase activity. Waved-2 mice also showed fewer renal tubular cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 42 publications
11
144
0
1
Order By: Relevance
“…1 Our previous studies in a UUO model demonstrated that EGFR activation contributes to a proinflammatory response and infiltration of inflammatory cells into the interstitium. 46 In the current study, inhibition of EGFR with gefitinib also reduced macrophage infiltration and expression of multiple proinflammatory cytokines/chemokines, including TNF-a, IL-6, MCP-1, and RANTES, in the kidney of hyperuricemic rats. Moreover, EGFR inactivation resulted in a decrease in renal phosphorylation of NF-kB induced by hyperuricemia.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…1 Our previous studies in a UUO model demonstrated that EGFR activation contributes to a proinflammatory response and infiltration of inflammatory cells into the interstitium. 46 In the current study, inhibition of EGFR with gefitinib also reduced macrophage infiltration and expression of multiple proinflammatory cytokines/chemokines, including TNF-a, IL-6, MCP-1, and RANTES, in the kidney of hyperuricemic rats. Moreover, EGFR inactivation resulted in a decrease in renal phosphorylation of NF-kB induced by hyperuricemia.…”
Section: Discussionsupporting
confidence: 57%
“…46 The densitometry analysis of immunoblot results was conducted using ImageJ software (National Institutes of Health, Bethesda, MD).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…15,16,32,33 In this regard, we recently reported that in a model of accelerated diabetic nephropathy (endothelial nitric oxide synthase-streptozotocin mice), administration of the EGFR tyrosine kinase inhibitor, erlotinib, markedly reduced albuminuria and glomerulosclerosis. 20 Similarly, studies in diabetic rats reported that a different EGFR tyrosine kinase inhibitor, PKI 166, attenuated early glomerular enlargement and preserved podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Boosting survival and regeneration of TECs might be renoprotective and antifibrotic as, for example, suggested for CSF-1 (143). Other TECs factors driving fibrosis include Notch (144), lipocalin-2 (NGAL) (28), kidney injury molecule-1 (KIM-1) (145), b-catenin signaling (146), and the EGFR (147,148). Paracrine signaling from damaged TECs is probably one of a major mechanisms driving renal fibrosis ( Figure 3).…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 98%